An analysis of the healthcare informatics and systems in Southeast Asia: A current perspective from seven countries - Nguyen, Quynh T.; Naguib, Raouf N.G.; Abd Ghani, Mohd Khanapi; Bali, Rajeev K.; Marshall, Ian M.; Phuong, Nguyen H.; Culaba, Alvin B.; Wickramasinghe, Nilmini S.; Shaker, Mohyi H.; Lee, Richard V. (Inderscience Enterprises Ltd, 2008)
This paper presents an overview of the healthcare systems in Southeast Asia, with a focus on the healthcare informatics developmentand deployment in seven countries, namely, Singapore, Cambodia, Malaysia, Thailand, Laos, the Philippines and Vietnam. Brief geographic and demographic information is provided for each country, followed by a historical review of the national strategies for healthcare informatics development. An analysis of the state-of-the-art healthcare infrastructure is also given, along with a critical appraisal of national healthcare provisions.